ATTITUDE TOWARDS TEACHING PROFESSIONALISM OF SECONDARY EDUCATION TEACHERS AT DOIMUKH EDUCATIONAL BLOCK OF ARUNACHAL PRADESH (CAHIERS MAGELLANES-NS, 2024)
A teacher’s teaching attitude is directly proportional to maintenance of teaching professionalism resulting in optimum educational results, and therefore the current study signifies to explore secondary education teacher’s attitude towards teaching professionalism. The study adopted a descriptive research, relevant data was collected with survey method by randomly selecting one hundred fifty (N = 150) secondary school teachers including both male (n = 74) and female (n = 76) from Govt.-aided & self-aided schools at Doimukh Educational Block of Arunachal Pradesh. Further, subjects were classified in terms of gender, qualifications, and type of schools. The findings of the study reveal that majority of secondary school teachers have showcased positive teaching attitude and teaching professionalism; a 50:50 in terms of classroom teaching attitude; majority have negative attitude for child-centred practices and education process; and majority indicated positive attitude to pupils and teachers scale, respectively. A significant difference in attitudes of teachers on gender basis towards teaching professionalism, classroom teaching, child-centred teaching practices and education process was found, whereas no significant difference among attitude of male and female teachers towards pupils and teachers scale was found. The findings of the study revealed that the teachers have negative attitude towards child-centered practices, and thus this study is significant as the problems raised in the study will help the institution heads to become more aware about the pertinent problems and to find remedial measures to improve the attitude of teachers towards teaching professionalism.